Taken for wonder nineteenth century travel writing from Iran to Europe - Sohrabi, Naghmeh (New York ; Oxford : Oxford University Press, 2012)
'Taken for Wonder' focuses on 19th-century travelogues authored by Iranians in Europe and argues for a methodological shift in the way scholars interpret travel writing.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Includes bibliographical references.
Keywords: Europe -- Description and travel; Europe -- Relations -- Iran; Iran -- Relations -- Europe; Travelers' writings, Persian -- Europe -- History and criticism; Iranians -- Europe -- History -- 19th century; Europe -- History -- 1789-1900.; Iran -- History -- Qajar dynasty, 1794-1925.